PAUD SEBAGAI PENANAMAN KARAKTER PEDULI LINGKUNGAN UNTUK MENCAPAI TARGET SUSTAINABLE DEVELOPMENT GOALS (SDGS) : SEBUAH STUDI LITERATUR: PAUD SEBAGAI PENANAMAN KARAKTER PEDULI LINGKUNGAN UNTUK MENCAPAI TARGET SUSTAINABLE DEVELOPMENT GOALS (SDGS) : SEBUAH STUDI LITERATUR - Ainin Shofiyah (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2022)
Abstract : Early childhood education is a coaching effort to shape children into good individuals through various educational stimuli. This is also inseparable from the importance of instilling good character. One of them is the character of love for the environment. which will have a sustainable impact considering children as a generation in life. Ensuring a healthy life by protecting the environment is one of the SDGs programs. Therefore the importance of awareness and concern for the surrounding environment that can benefit nature as a form of development. It is also based on natural phenomena such as natural disasters and environmental damage caused by various natural or non-natural and human factors. So that the urgency of the need for awareness to all elements of society must be carried out from the bottom and in a sustainable manner. Therefore, education is expected to be an approach to instilling the character of a love for the environment in children from an early age. This study uses a literature review approach to look at ideas about early childhood education in instilling environmental love characters in children to achieve the target of Sustainable Development Goals (SDGs). This study argues that the importance of inculcating a love for the environment in children through early childhood education can be an approach to achieving the target of Sustainable Development Goals (SDGs). Keywords: ECE, Environmental Love Character, Sustainable Development Goals (SDGs)